Efficacy of an experimental dentifrice formulation on primary school children in Ga-Rankuwa, Pretoria - Gugushe, T S; de Wet, F A; Rojas-Silva, O (The Journal of the Dental Association of South Africa = Die Tydskrif van die Tandheelkundige Vereniging van Suid-Afrika, 1994)
The purpose of this study was to assess the efficacy of a dentifrice containing 1 per cent chlorhexidine gluconate at reducing plaque formation and gingival inflammation over a 12 week period. The effects of the test toothpaste were compared with control and conventional dentifrices in a randomised double-blind clinical trial of parallel design. Following baseline examination at which gingival and plaque indices (GI and PI) were measured, 156 primary school children were assigned to one of three groups that were matched for age, gender, GI and PI. After plaque control instruction the pupils were requested to use the dentifrice twice daily. After 6 and 12 week intervals the PI and GI were reassessed. There was no significant difference in GI between groups. The PI was significantly lower (p < 0.002) after use of the chlorhexidine containing dentifrice compared with the other two products.